Surface-confined formation of conjugated porphyrin-based nanostructures on Ag(111). Issue 47 (29th November 2021) - Cao, Nan; Riss, Alexander; Corral-Rascon, Eduardo; Meindl, Alina; Auwärter, Willi; Senge, Mathias O.; Ebrahimi, Maryam; Barth, Johannes V.
Abstract : On the Ag(111) surface and mediated by temperature, McMurry coupling resulted in the construction of conjugated porphyrin nanostructures linked by CC, which were identified by high resolution STM and nc-AFM images and XPS. Abstract : Porphyrin-based oligomers were synthesized from the condensation of adsorbed 4-benzaldehyde-substituted porphyrins through the formation of CC linkages, following a McMurry-type coupling scheme. Scanning tunneling microscopy, non-contact atomic force microscopy, and X-ray photoelectron spectroscopy data evidence both the dissociation of aldehyde groups and the formation of CC linkages. Our approach provides a path for the on-surface synthesis of porphyrin-based oligomers coupled by CC bridges – as a means to create functional conjugated nanostructures.